Green Infrastructure Can Improve the Lives of Slum Dwellers in African Cities - Adegun, Olumuyiwa Bayode (Frontiers in Sustainable Cities, 2021)
 Slums and informal settlements in African cities are notably connected to green spaces and natural ecosystems serving as green infrastructure.  Green Infrastructure holds potential for improvement in quality of life and environmental quality by harnessing benefits for livelihoods, food security, environmental regulation, socio-cultural appropriation etc, and addressing constraints to greening.  Policy initiatives and relevant greening programmes, especially those utilizing participatory, low-cost, socio-economically empowering approaches are recommended.